Thiolate-Protected Au25(SC2H4Ph)18 Nanoclusters as a Catalyst for Intermolecular Hydroamination of Terminal Alkynes - Nagata, Tatsuki; Adachi, Yurina; Obora, Yasushi (Synlett, 2018)
Au25(SC2H4Ph)18 nanoclusters have high catalytic activity for hydroamination of terminal alkynes. This reaction proceeds under O2 or air. The presence of molecular oxygen has a profound effect on the Au25(SC2H4Ph)18 reactivity. The catalysts can be separated from the mixture after the reaction and reused.
Keywords: hydroamination; gold nanocluster; imines; gold catalyst; reusing catalyst